2003
DOI: 10.1016/s0741-5214(03)00470-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon specialty and provider volumes are related to outcome of intact abdominal aortic aneurysm repair in the united states

Abstract: High surgeon volume and hospital volume of AAA repair were both associated with lower mortality compared with low-volume providers. Increased specialization in vascular surgery was associated with markedly decreased mortality independent of AAA repair volume. Health policy in support of selective referral for AAA repair should consider surgical specialization in addition to provider volume thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
141
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(151 citation statements)
references
References 18 publications
(53 reference statements)
2
141
2
4
Order By: Relevance
“…In fact, in a recent analysis, both a high surgeon volume and a high hospital volume were both associated with lower mortality than low-volume providers and that surgeons specializing in vascular surgery had a lower mortality than did nonspecialized surgeons with the same aortic repair volume. 50 A less-invasive alternative to open surgery for repair of abdominal aortic aneurysms is the use of percutaneously implanted, expanding endovascular stent-grafts. Once deployed, the stent-graft serves to bridge the region of the aneurysm, thereby excluding it from the circulation while allowing aortic blood flow to continue distally through the prosthetic stent-graft lumen.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In fact, in a recent analysis, both a high surgeon volume and a high hospital volume were both associated with lower mortality than low-volume providers and that surgeons specializing in vascular surgery had a lower mortality than did nonspecialized surgeons with the same aortic repair volume. 50 A less-invasive alternative to open surgery for repair of abdominal aortic aneurysms is the use of percutaneously implanted, expanding endovascular stent-grafts. Once deployed, the stent-graft serves to bridge the region of the aneurysm, thereby excluding it from the circulation while allowing aortic blood flow to continue distally through the prosthetic stent-graft lumen.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Studies have shown that high caseloads can lead to better outcomes and lower complication rates in subarachnoid hemorrhage, epilepsy surgery, pediatric brain tumor, and other surgical fields. 3,10,14,16,18,20,41 One would anticipate complication rates to be greater at LVCs across the board, but this has not been proven in the literature. In fact, the complication rate for DBS has remained small even as more LVCs have arisen.…”
Section: Discussionmentioning
confidence: 99%
“…2, 9, 10) While certain high-volume centers of excellence report very low mortality rates (from 0% to 1.2%), 3,11,12) multi-institutional nationwide data continue to show significantly higher incidence of mortality ranging between 4.2% and 8.4%. 11,12) This discrepancy has been seen as a result of the case volume related difference in outcome. Many reports have identified a strong relationship between the operative outcome and case volume of the individual surgeon or the institution.…”
Section: Discussionmentioning
confidence: 99%